2019
DOI: 10.3389/fphys.2019.00563
|View full text |Cite
|
Sign up to set email alerts
|

Dysmaturation of Somatostatin Interneurons Following Umbilical Cord Occlusion in Preterm Fetal Sheep

Abstract: Introduction Cerebral white matter injury is the most common neuropathology observed in preterm infants. However, there is increasing evidence that gray matter development also contributes to neurodevelopmental abnormalities. Fetal cerebral ischemia can lead to both neuronal and non-neuronal structural-functional abnormalities, but less is known about the specific effects on interneurons. Objective In this study we used a well-established animal model of fetal asphyxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
5
12
0
Order By: Relevance
“…In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations. These findings are broadly consistent with previous studies showing loss and disrupted development of interneurons in the cerebral cortex and subcortical grey matter following HI in preterm and term fetal sheep [17,[32][33][34][35] and neonatal rodents [36][37][38][39][40][41][42][43] and following ventilatory support in preterm baboons [44]. Although there are no comparable term human data, limited pathology and imaging studies in preterm infants have shown reductions in the numbers and complexity of cortical interneurons, refs [25,45] cortical interneuron migration, [7] interneuron neurogenesis, [46] and cortical GABAergic signaling [4].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations. These findings are broadly consistent with previous studies showing loss and disrupted development of interneurons in the cerebral cortex and subcortical grey matter following HI in preterm and term fetal sheep [17,[32][33][34][35] and neonatal rodents [36][37][38][39][40][41][42][43] and following ventilatory support in preterm baboons [44]. Although there are no comparable term human data, limited pathology and imaging studies in preterm infants have shown reductions in the numbers and complexity of cortical interneurons, refs [25,45] cortical interneuron migration, [7] interneuron neurogenesis, [46] and cortical GABAergic signaling [4].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies that showed susceptibility of interneurons to perinatal insults in animal models and post-mortem human tissue, we observed differences in interneuron density following induction of EoP in both our models [ 19 , 20 , 21 , 23 , 24 , 25 , 62 ]. However, the previous published studies generally use single-hit (fetal/postnatal inflammation or hypoxia) models, failing to reflect the multifactorial etiology of EoP [ 19 , 23 , 24 , 25 , 26 , 27 ]. Furthermore, it is good to note that different studies have used different markers of subpopulations of interneurons.…”
Section: Discussionsupporting
confidence: 92%
“…The net absence of GAD67+ abnormalities in our mouse model might be explained by the overshoot of VIP-expressing interneurons, masking the maturation arrest of PV+ cells. Additional evidence for interneuron maturational arrest of interneurons can be found in other preclinical studies [ 19 , 23 ]. In the first postnatal weeks, similar to excitatory neurons, a surplus of interneurons is eliminated via inactivity-dependent programmed cell death, leading to circuit refinement [ 16 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In a study of partial uterine artery occlusion, modeling hypoxia-ischemia in the fetal sheep, immediate low level necrotic cell death was found throughout the deep and cortical GM, followed by extensive apoptosis in both the GM and WM at 3 h post-injury ( 131 ). Other studies of in utero hypoxia-ischemia in sheep have shown some increase in pyknotic cells and activated caspase-3 staining from 24 h up to 4 weeks in the caudate nucleus and subplate ( 132 , 133 ), reduced NeuN and somatostatin positive neurons in the caudate and putamen ( 134 ), specific loss of glutamate decarboxylase interneurons (a marker of GABAergic neurons) and their perineuronal nets in the cortex ( 135 ), along with reduced arborization complexity and spine density in both the caudate, hippocampus, and cortex ( 103 , 132 134 , 136 ).…”
Section: Animal Models Of Gm Pathologymentioning
confidence: 97%